Consensus of Russian experts on the evaluation of arterial stiffness in clinical practice - Yu. A. Vasyuk; S. V. Ivanova; E. L. Shkolnik; Yu. V. Kotovskaya; V. A. Milyagin; V. E. Oleynikov; Ya. A. Orlova; A. N. Sumin; A. A. Baranov; S. A. Boytsov; A. S. Galyavich; Zh. D. Kobalava; et al. (Кардиоваскулярная терапия и профилактика)
Recently, there was plenty studies published on the arterial stiffness assessment, and importance of this was proved as an independent prediction parameter, together with standard cardiovascular risk factors. In current document, we collect and structure the available clinical and scientific data from abroad and Russian studies. The aim of current publication is the need to bring a reader the importance of demanded in clinical practice ways of arterial wall stiffness assessment, information about conditions when it is important to the assessment, and available restrictions, as the issues remaining unresolved.